Raw material criticality assessment as a complement to environmental life cycle assessment: Examining methods for product‐level supply risk assessment - Cimprich, Alexander; Bach, Vanessa; Helbig, Christoph; Thorenz, Andrea; Schrijvers, Dieuwertje; Sonnemann, Guido; Young, Steven B.; Sonderegger, Thomas; Berger, Markus (Journal of industrial ecology, 2019)
Summary The diversity of raw materials used in modern products, compounded by the risk of supply disruptions—due to uneven geological distribution of resources, along with socioeconomic factors like production concentration and political (in)stability of raw material producing countries—has drawn attention to the subject of raw material “criticality.” In this article, we review the state of the art regarding the integration of criticality assessment, herein termed “product‐level supply risk assessment,” as a complement to environmental life cycle assessment. We describe and compare three methods explicitly developed for this purpose—Geopolitical Supply Risk (GeoPolRisk), Economic Scarcity Potential (ESP), and the Integrated Method to Assess Resource Efficiency (ESSENZ)—based on a set of criteria including considerations of data sources, uncertainties, and other contentious methodological aspects. We test the methods on a case study of a European‐manufactured electric vehicle, and conclude with guidance for appropriate application and interpretation, along with opportunities for further methodological development. Although the GeoPolRisk, ESP, and ESSENZ methods have several limitations, they can be useful for preliminary assessments of the potential impacts of raw material supply risks on a product system (i.e., “outside‐in” impacts) alongside the impacts of a product system on the environment (i.e., “inside‐out” impacts). Care is needed to not overlook critical raw materials used in small amounts but nonetheless important to product functionality. Further methodological development could address regional and firm‐level supply risks, multiple supply‐chain stages, and material recycling, while improving coverage of supply risk characterization factors.